Hold-Up and the Use of Performance-Sensitive Debt - Tim R. Adam; Daniel Streitz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
We examine whether performance-sensitive debt (PSD) is used to reduce hold-up problems in long-term lending relationships. We find that the use of PSD is more common in the presence of a long-term lending relationship and if the borrower has fewer financing alternatives available. In syndicated deals, however, the presence of a relationship lead arranger reduces the use of PSD, which is consistent with hold-up being of lesser concern in such cases. Further, supporting our hypothesis that hold-up concerns motivate the use of PSD, we find a substitution effect between the use of PSD and the tightness of financial covenants.
Keywords: G21; G31; G32; 330; Performance-sensitive debt; relationship lending; hold-up; holdout; syndicated debt; covenants